A sub-national economic complexity analysis of Australia's states and territories. Issue 5 (4th May 2018) - Reynolds, Christian; Agrawal, Manju; Lee, Ivan; Zhan, Chen; Li, Jiuyong; Taylor, Phillip; Mares, Tim; Morison, Julian; Angelakis, Nicholas; Roos, Göran
ABSTRACT: A sub-national economic complexity analysis of Australia's states and territories. Regional Studies . This paper applies economic complexity analysis to the Australian sub-national economy (nine regions with 506 exported goods and services). Using a 2009 Australian multi-regional input–output table for base data, we determine the number of export goods or services in which each state and territory has a revealed comparative advantage, and visualize the complexity of Australia's interstate and international exports. We find that small differences in industrial capability and knowledge are crucial to relative complexity. The majority of states (especially Western Australia) export primarily resource-intensive goods, yet interstate trade has many complex products that are not currently internationally exported.